Climate risk and farming systems in rural Cameroon - Rudolf Witt; Hermann Waibel (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2009)
Climate risk is particularly burdensome to small-scale farmers in developing countries due to heavy dependence on natural resources, limited and erratic rainfall with high inter- and intra-annual variability, and other natural calamities. Numerous studies on climate change suggest that climate variability is expected to increase in the next few decades, and that it is likely to be severe for tropical areas. For the design of better intervention strategies that are capable to stabilize the incomes of the poor and decrease vulnerability, it is mandatory to have a good understanding of the livelihoods of rural populations, and the risks they are facing. This paper presents an approach to measuring climate risk and its impact on livelihood outcomes in fishery-dependent communities in the ya'eres floodplain (Far North Province of Cameroon) by applying portfolio theory and stochastic dominance rules. The focus of the analysis is put on the question, how portfolio decisions of households affect income and risk in different production systems. Assuming possible future scenarios we can derive approximate predictions of the effects of climate change and rural development interventions on income and the 'riskiness' of different activity portfolios. The results suggest that the diversification effect in the study area is limited due to high correlation of income flows from different activities. However, we show that development intervention strategies, which particularly aim at changing the covariation structure of income flows, are most successful in reducing risk, and potentially increasing income.
Keywords: G11; Q12; Q54; 330; Climate risk; agricultural diversification; portfolio theory; Sub Saharan Africa; Klimaveränderung; Agrareinkommen; Risiko; Binnenfischerei; Landwirtschaftliches Betriebssystem; Diversifikation; Portfolio-Management; Kamerun; Afrika südlich der Sahara